Pengaruh Pertumbuhan Penjualan, Struktur Aset, Risiko Bisnis, dan Ukuran Perusahaan terhadap Struktur Modal dengan Profitabilitas Sebagai Variabel Moderasi - Shiva Angelica; Liza Novietta; Ruswan Nurmadi (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to analyze the effect of Sales Growth, Asset Structure, Business Risk, and Company Size on Capital Structure, with Profitability as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018-2022. The type of research conducted is quantitative with a causal associative approach. The study population includes all manufacturing companies listed on the IDX during that period. Sampling was carried out using the purposive sampling method, resulting in 66 companies observed for five consecutive years, so that the total sample obtained was 330. The analysis methods applied in this study include Descriptive Statistical Analysis, Classical Assumption Test, Hypothesis Test, Multiple Linear Regression Analysis, and Moderated Regression Analysis (MRA). The results of the study indicate that Sales Growthand Asset Structure have a significant effect on Capital Structure, while Business Risk and Company Size do not affect Capital Structure. In addition, Profitability cannot moderate the relationship between Sales Growth, Asset Structure, Business Risk, and Company Size on Capital Structure.